158k views
1 vote
PLEASE HELP!!!!!!!!!!!!!

PLEASE HELP!!!!!!!!!!!!!-example-1
User Mirela
by
5.8k points

1 Answer

4 votes

Answer:

A

Explanation:

Given

y = x² + 2

Substitute the x value from an ordered pair from each table into the equation and compare the value obtained with the y value of the ordered pair

Table A

using (- 2, 6 )

y = (- 2)² + 2 = 4 + 2 = 6 ← this corresponds to the y value of the ordered pair

Table B

Using (- 2, - 2)

y = (- 2)² + 2 = 4 + 2 = 6 ≠ - 2 ← thus not a solution

Table C

Using (- 2, - 2)

y = (- 2)² + 2 = 4 + 2 = 6 ≠ - 2 ← thus not a solution

Thus Table A gives the solutions to y = x² + 2

User Yassassin
by
6.1k points